Cold-water corals in decline – A temporal (4 year) species abundance and biodiversity appraisal of complete photomosaiced cold-water coral reef on the Irish Margin. (April 2019) - Boolukos, Corie M.; Lim, Aaron; O'Riordan, Ruth M.; Wheeler, Andrew J.
Abstract: Scleractinian cold-water corals (CWCs), such as Lophelia pertusa and Madrepora oculata, build complex frameworks and carbonate mound habitats in the deep-sea and are regarded as deep-sea biodiversity hotspots. However, there is a paucity of research regarding temporal change in the biological composition of these CWC habitats and analysis of this change is critical, especially considering the anthropogenic influences impacting upon these vital habitats. This study is the first to analyse temporal biological change on a CWC mound at a small temporal (4 years) and large spatial (entire mound) scale. Video datasets were collected over the Piddington Mound of the Moira Mounds, Porcupine Seabight, offshore Ireland, in 2011 and 2015. 0.25 m 2 quadrats were placed on 510 screenshots from each year (1020 total). Species were identified and quantified. CTD data were also analysed to investigate potential contributory causes of change. There was a highly significant (P < 0.01) decline in average M. oculata percentage cover from 2011 (1.37 ± 3.79%) to 2015 (0.70 ± 2.76%); however, there was not a significant change (P = 0.74) in average L . pertusa percentage cover in 2011 (2.33 ± 7.52%) when comparing it with 2015 (5.28 ± 7.88%). Additionally, there was an increase in average percentage cover of two poriferan species, Aphrocallistes sp. and Hexadella sp., from 2011 (1.18 ± 2.35%; 0.21 ± 0.42%, respectively) to 2015 (2.15 ± 3.48%; 0.33 ± 0.55%, respectively) (P < 0.01 for both species). Shannon-Weiner and Pielou's Species Evenness diversity indices were generally higher in 2011 than in 2015. This overall decline in diversity and increase in poriferan abundances is attributed to the decline in M. oculata, which may have been influenced by altered environmental conditions in 2015, as indicated by the CTD data. Moreover, differing biological and ecological responses of L . pertusa and M. oculata to environmental changes were considered and discussed as possible contributors to the results observed for these two species. If M. oculata percentage cover declines linearly at the current rate (approximately 0.17% per year, if a constant decline in each of the four years), then by 2019, this species may be nearly absent from the Piddington Mound, which would have major effects on species' abundances, distributions, and biodiversity. Therefore, further research and continuous monitoring of the temporal change in biological composition within CWC reef/mound habitats are critical. Highlights: 34 species and morphospecies encompassing 7 phyla were identified on a CWC mound. Average percentage cover of Madrepora oculata declined significantly over 4 years. Average percentage cover of two sponge species increased significantly over 4 years. Temporal change in water temperature and salinity was found around the CWC mound.